High-repetition rate picosecond laser-induced damage properties of Ta2O5:SiO2 coatings - Zhang, Mingxiao; Qiu, Fumin; Qiao, Zhao; Zhou, Qiang; Pu, Yunti; Xiong, Bingcheng; Die, Junhui; Lv, Liang; Ma, Ping (Frontiers in Physics, 2022)
High repetition rate picosecond Laser induced damage properties of Ta2O5:SiO2 mixture coatings were investigated at wavelength of 355nm and repetition rate of 30KHz. The laser induced damage thresholds (LIDT) of the coatings with different mixture ratio were measured. The relationship of LIDT and both of the material band gap and defect absorption was analyzed. With the increase of the laser pulse numbers, the LIDT decreased as a result of the enhancement of the absorption. We attributed the enhancement of absorption to the density increase of the mid-sated defects induced by the picosecond laser pulses. The connection of the mid-state defects and materials mixture ratio was also analyzed in this paper.